Linguistics Lanscape In Beringkit Public Market - I Gusti Bagus Wahyu Nugraha Putra; Devi Maharani Santika, I Dewa Ayu (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
This research discusses about the presence of Linguistic Landscape in Beringkit Public Market. Linguistic Landscape concerned with the use of textual language displayed in public spaces. Formatted languages include the use of language on various signs and the focus of Linguistic Landscape studies does not focus on just one language, but bilingualism or multilingualism. Beringkit Public Market is one of the traditional market located at Kebo Iwa Street, Mengwi subdistrict, Badung Regency, Bali Province. Descriptive Qualitative method was applied in this research in other to analyze the data. The data were collected through direct observation with photographic technique. As the result, it was found that 39 signs consider as the representation of advertising signs based on the function and usefulness. In term of the language use 39 signs (65%) are in Indonesian.